1992
DOI: 10.1152/ajpgi.1992.262.4.g695
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a putative nonadrenergic noncholinergic inhibitory transmitter in the canine pylorus in vivo

Abstract: Antropyloroduodenal motility was recorded in seven anesthetized dogs to assess the role of nitric oxide and L-arginine metabolites in nonadrenergic noncholinergic (NANC) mediation of pyloric relaxation. Pyloric activity induced by duodenal field stimulation was inhibited by antral field stimulation and electrical vagal stimulation. Intra-arterial NG-L-arginine-methyl-ester (L-NAME) reduced the inhibition from antral or vagal stimulation (P less than 0.05). Intravenous infusion of L-NAME also blocked the inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 0 publications
7
44
0
2
Order By: Relevance
“…Table 2. Effect of several autonomic drugs and NO related agents on NANC relaxations induced by EFS (5 Hz, 3.0 msec, 100 V, 10 sec trains) in the mouse whole stomach DISCUSSION Many reports have so-far concerned the role of NO in mediating NANC relaxation of isolated gastric smooth muscle in animal species such as rats (15,16), cats (23), dogs (24), guinea pigs (17)(18)(19) and ferrets (25). At present, however, no knowledge is available about the NANC inhibitory response in the mouse stomach.…”
Section: Effect Of Nos Inhibitors Hemoglobin and Methylene Blue On Tmentioning
confidence: 99%
“…Table 2. Effect of several autonomic drugs and NO related agents on NANC relaxations induced by EFS (5 Hz, 3.0 msec, 100 V, 10 sec trains) in the mouse whole stomach DISCUSSION Many reports have so-far concerned the role of NO in mediating NANC relaxation of isolated gastric smooth muscle in animal species such as rats (15,16), cats (23), dogs (24), guinea pigs (17)(18)(19) and ferrets (25). At present, however, no knowledge is available about the NANC inhibitory response in the mouse stomach.…”
Section: Effect Of Nos Inhibitors Hemoglobin and Methylene Blue On Tmentioning
confidence: 99%
“…NO synthase (NOS) is present in the gastrointestinal nervous system, and NO has been proposed as a non-adrenergic non-cholinergic (NANC) mediator (3). Inhibition of NO production inhibits proximal stimuli-induced pyloric relaxation and enhances distal stimuli-induced pyloric excitation in anesthetized dogs (4). In addition, intravenous administration of N G -nitro-L-arginine (L-NNA) prolongs the gastric emptying time in conscious dogs (5), and our previous study reported that the oral administration of L-NNA induced a delay in gastric emptying in rats (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that metabolites of L-arginine mediate neuronal inhibition of canine pyloric motor activity in vivo (Allescher et al, 1992) and facilitate gastric emptying by inhibiting pyloric contractions (Orihata and Sarna, 1994). Gastric distension-induced pyloric relaxation appears to be mediated via a vago-vagal reflex and NO release in the rat (Ishiguchi et al, 2001).…”
mentioning
confidence: 99%